Regulation of Kv1.4 potassium channels by PKC and AMPK kinases. Issue 1 (1st January 2018) - Andersen, Martin Nybo; Skibsbye, Lasse; Saljic, Arnela; Larsen, Martin Zahle; Rasmussen, Hanne Borger; Jespersen, Thomas
ABSTRACT: Over the last years extensive kinase-mediated regulation of a number of voltage-gated potassium (Kv) channels important in cardiac electrophysiology has been reported. This includes regulation of Kv1.5, Kv7.1 and Kv11.1 cell surface expression, where the kinase-mediated regulation appears to center around the ubiquitin ligase Nedd4-2. In the present study we examined whether Kv1.4, constituting the cardiac Ito, s current, is subject to similar regulation. In the epithelial Madin-Darby Canine Kidney (MDCK) cell line, which constitutes a highly reproducible model system for addressing membrane targeting, we find, by confocal microscopy, that Kv1.4 cell surface expression is downregulated by activation of protein kinase C (PKC) and AMP-activated protein kinase (AMPK). In contrast, manipulating the activities of phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) and serum and glucocorticoid-regulated kinase 1 (SGK1) were without effect on channel localization. The PKC and AMPK-mediated downregulation of Kv1.4 membrane surface localization was confirmed by two-electrode voltage clamp in Xenopus laevis oocytes, where pharmacological activation of PKC and AMPK reduced Kv1.4 current levels. We further demonstrate that unlike related Kv channels, Kv1.4 current levels in Xenopus laevis oocytes are not reduced by co-expression of Nedd4-2, or the related Nedd4-1 ubiquitin ligase. In conclusion, we demonstrate that the surface expression of Kv1.4 is downregulated by the two kinases AMPK and PKC, but is unaffected by PI3K-SGK1 signaling, as well as Nedd4-1/Nedd4-2 activity. In the light of previous reports, our results demonstrate an impressive heterogeneity in the molecular pathways controlling the surface expression of highly related potassium channel subunits.